Kajian Kadar Lumpur pada Model Infiltrasi Buatan dengan Variasi Kemiringan Tanah dan Tanaman - Usep Supriatna (Universitas Muhammadiyah Yogyakarta, 2013)
From various soil conditions, there are need some efforts to restore soil functions as a water absorbent that is expected to reduce the excessive surface runoff indirectly and to increase infiltration. The purpose of this study was to calculate Total Suspended Solid (TSS) level on artificial infiltration model using the three media (grassland, krokot land, and vacant land) with the variation slope of 5°, 10°, 15° and 20°. This research also to understand the influence of soil media variety and land slope on TSS of artificial infiltration model. This research was carried out by preparing an artificial wood model with size 200 cm x 150 cm x 100 cm, which was then divided into three parts with each of them is 200 cm x 50 cm x 100 cm and used for soil media placement. The discharged water used in all three media was the same that is equal to 0.237ℓ/sec. For the results representative in each study, 100 mℓ of water samples can be taken in the runoff on the model for each soil media and then immediately examined the levels of TSS in the laboratory. According to the variation slope, the results of the research showed that the TSS on the grass soil media was 4700 mg/ℓ, 9200 mg/ℓ, 9500 mg/ℓ and 10 000 mg/ℓ. For krokot soil, the TSS was 6500 mg/ℓ, 66000 mg/ℓ, 126000 mg/ℓ and 273 900 mg/ℓ, while for vacant land was 5100 mg/ℓ, 101500 mg/ℓ, 109500 mg/ℓ and 243600 mg/ℓ. Furthermore, the steeper the lands slope, the higher TSS.